A dynamic submerging motion model of the hybrid-propelled unmanned underwater vehicle: Simulation and experimental verification - Talarczyk, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
Hybrid propulsion in underwater vehicles is the new idea of combining conventional propulsion systems such as screw propellers with other kinds of propulsion like oscillating biomimetic fins, glider wings or jet thrusters. Each of these propulsion systems has its own benefits and drawbacks, and the goal is to have them complement each other in certain conditions.
Keywords: autonomous underwater vehicles; hybrid propulsion system; biomimetic underwater vehicles; dynamic diving; diving model